Konsep Creatio Ex Nihilo Pada Dinding Mural di Kehidupan 4.0 Sang Imago Dei - Maria Patricia Tjasmadi (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2021)
The Latin phrase ex nihilo has the meaning "from nothing". In religious science, this phrase usually appears together with the concept of creation. Therefore, creatio ex nihilo can be interpreted as "creation that emerged from nothing". This concept is important for Christian educators in schools and churches. Through the Self-Development course, it is known that 80% of students are not convinced by the appearance of the picture of their life in the 4.0 era. Therefore, by researching literacy data and the Bible, this concept is expected to be a compass in achieving students' learning goals so that they are able to see the magnitude of God's power and ready to paint it on this digital wall of life. The wall of life that was originally empty must be filled with a picture of a person with the title Imago Dei. A picture that now and in the future will be enjoyed by relatives, students, children, and grandchildren, entrusted by God. Can a picture life displayed on social media becomes an example for the next generation?